Acupuncture for Primary Dysmenorrhea: An Overview of Systematic Reviews. (21st November 2018) - Zhang, Furong; Sun, Mingsheng; Han, Shanshan; Shen, Xiaoyu; Luo, Yanan; Zhong, Dongling; Zhou, Xiujuan; Liang, Fanrong; Jin, Rongjiang
Abstract : Objectives . As current evidence of the effectiveness on acupuncture for primary dysmenorrhea (PD) is inconsistent, we aimed to critically appraise the evidence from relevant systematic reviews (SRs). Methods . SRs of randomized controlled trials (RCTs) concerning acupuncture and PD were searched in four databases. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and latest Assessment of Multiple Systematic Reviews 2 (AMSTAR2) checklists were used to assess reporting characteristics and methodological quality, respectively. Results . The literature search yielded 38 potential records, of which five met the inclusion criteria. The total average (SD) for PRISMA was 20.60 (1.14) out of 27. All five SRs have more than one critical weakness in AMSTAR2, so their methodological qualities were considered as critically low. The most frequent problems included nonregistration of study protocol, absence of a list of excluded studies, and unclear acknowledgment of conflicts of interests. The three studies of higher methodological quality reported positive results in pain relief. Conclusion . The reporting and methodological quality of systematic reviews and meta-analysis studies were suboptimal, which demands further improvement. More efforts are needed to improve validity of systematic reviews and RCTs in this area.